Morphological changes in placenta in cases of oligohydramnios - Gupta, Amita; Musharaf, Sabha; Singh, Gagan; Gupta, Aakriti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: There are gross and microscopic changes in placenta and umbilical cord in complicated pregnancies. The objective of this study was to study pathological (gross and microscopic) changes in placenta, membrane and umbilical cord in cases with oligohydramnios and to study relationship between changes in placenta, membranes and umbilical cord with severity of oligohydramnios. Methods: A total of 50 patients were selected and their placentas were collected after delivery and sent to pathology department in 10 % formalin for histopathological examination. Patients were divided into three groups and the results were compared. Statistical calculations were performed using the SPSS 16.0. In order to detect differences between subjects students t-test was used for continuous variables, while, for categorical variables, the X2 test was used. A p-value of less than 0.05 was considered statistically significant. Results: Atotal of 50 patients were studied for a period of one year and following observations were made, discoid shape placenta in 45 (90.0%), oval in 5 (10.0%), central attachment of umbilical cord in 16 cases (32.0%), eccentric in 33 (66.0%), marginal in 1 (2.0%) case following variables were compared and p value detected, placental maximum diameter (p <0.0001),placental minimum diameters (p = 0.041), mean of cord length (p <0.0001) placental weight (p = 0.273), placental thickness (p = 0.253), acute chorioamnionitis (p <0.0001), chronic chorioamnionitis (p<0.0001), focal squamous metaplasia (p <0.0001), bacterial colonies in subamnion (p <0.0001), meconium staining (p <0.0001), amnion nodosum (p < 0.0001), intra amniotic haemorrhage (p = 0.090), membranous deciduitis with chorioamnionitis (p = 0.081), focal haematoma (p = 0.010), acute inflammatory infiltrate in Wharton’s jelly (p = 0.012), single umbilical artery (p =0.010), intervillous fibrin deposition (p <0.0001), calcification (p<0.0001), chorangiosis (p <0.0001), syncytial knots (p <0.0001), avascular villi (p = 0.011), villous edema (p = 0.090) and infarct (p = 0.090). Conclusions: There are alterations in placental morphology associated with oligohydramnios hence placenta should be examined, which may be useful in predicting perinatal morbidity and mortality.